CAUSATIVE FACTOR OF DELAY IN MATERNAL REFERRAL - SYSTEMATIC REVIEW - Sarlita Rahmi Amalia; Pudji Lestari; Astika Gita Ningrum (UNIVERSITAS AIRLANGGA, 2022)
Background: Every day in the world, around 810 mothers have died from preventable causes. The causes of delay in maternal referral care were analyzed using the Three Delay Model (Thaddeus & Maine, 1994) and the determinants of maternal mortality (McCarthy & Maine, 1992). Purpose: To describe the factors that causing delays in seeking care for maternal referrals. Methods: This is a systematic review study of articles published between 2010 and 2020 based on database from ScienceDirect, Scopus, SageJournals, and Google Scholar. Nine articles that met the inclusion and exclusion criteria were included as samples for further review. The results regarding the factors causing late referral are described and explained in narrative form. Results: First delay (8 articles), Second delay (5 articles), Third delay (4 articles), mother’s education (6 articles), mother's income and occupations (2 articles), women's empowerment (6 articles), family status in society (4 articles), community status (3 articles), and cultural influences (7 articles) studies are acquired. Conclusions: The previous delay will affect the next delay and the problem of delay in seeking health care is in decision-making which mostly found in upper-middle countries, the causes of cultural factors which also causing the delay in referrals, followed by the socioeconomic influence that most widely discussed are maternal education and women's empowerment, the problem which is also most commonly found in upper-middle-income countries.